Interview with Nicola Emery - Nicola Emery; Filippo Angelucci; Pietromaria Davoli (Techne)
The contribution proposes to think about the antinomies of enabling technologies, the paradox of a 'facilitation' that exempts mankind not only and not so much from the fatigue of material labour (which remains hidden but persists) but also and more drastically from the possibility of the moral freedom of choice and refusal. If, in the contemporary framework, nothing less than the possibility of deciding the purpose of doing is in danger of falling, if the purpose always seems to be decided in advance by the totalising logic of the process at work, we must remain vigilant about the cost in terms of the metamorphosis of the critical and authentically projectual rationality of 4.0 era.